Extradenticle raises the DNA binding specificity of homeotic selector gene products. - van Dijk, M.A.; Murre, C. (Cell, 1994)
Recently, a Drosophila gene has been identified, extradenticle, whose product modulates the morphological consequences of homeotic selector genes. We show here that extradenticle protein raises the DNA binding specificity of Ultrabithorax and abdominal-A but not that of Abdominal-B. We further show that extradenticle modulates the DNA binding activity of engrailed to a different target site. While a region N-terminal of the extradenticle homeodomain is required for Ultrabithorax and abdominal-A cooperativity, engrailed requires a domain C-terminal of the extradenticle homeobox. These studies show directly how the DNA binding specificity of selector gene products can be raised by extradenticle and provides a mechanism, cooperative DNA binding, that allows selector gene products to achieve some of their biological specificity.